Lacomo: A Layer to Develop Collaborative Mobile Applications - Pichiliani, Mauro Carlos; Dewan, Prasun; Massaki Hirata, Celso (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2019: Anais do XV Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2019.7819, 2019)
Nowadays, there is little support for developers to transform single user applications to collaborative ones in the mobile domain. We present Lacomo, a new software layer to build collaborative mobile applications with accessibility, screen sharing, and application rewriting technologies that reduce costs to prototype collaboration features, thereby increasing the range of supported applications without deep application knowledge. We compare it to an ad hoc approach. Users using Lacomo performed a testing task faster, with less effort and errors at a higher completion time.